Strategies to Improve the Thermoelectric Figure of Merit in Thermoelectric Functional Materials - Sun, Yan; Liu, Yue; Li, Ruichuan; Li, Yanshuai; Bai, Shizheng (Frontiers in Chemistry, 2022)
In recent years, thermoelectric functional materials have been widely concerned in temperature difference power generation, electric refrigeration and integrated circui, and so on. In this paper, the design and research progress of thermoelectric materials around lifting ZT value in recent years are reviewed. Optimizing the carrier concentration to improve the Seebeck coefficient, the steady improvement of carrier mobility and the influence of energy band engineering on thermoelectric performance are discussed. In addition, the impact of lattice thermal conductivity on ZT value is also significant. We discuss the general law that the synergistic effect of different dimensions, scales, and crystal structures can reduce lattice thermal conductivity, and introduce the new application of electro-acoustic decoupling in thermoelectric materials. Finally, the research of thermoelectric materials is summarized and prospected in the hope of providing practical ideas for expanding the application and scale industrialization of thermoelectric devices.